Differentiated approach to the treatment of musculoskeletal pain: higher doses of analgesics provide a better effect. A brief narrative review - A. E. Karateev; A. M. Lila (Современная ревматология)
Effective pain control is one of the main goals in the treatment of patient with musculoskeletal disorders. The main suffering of patients is associated with pain: decrease in working capacity and quality of life, disability and severe psycho-emotional disturbances. The pathogenesis of musculoskeletal pain is complex and includes damage (due to an autoimmune process, mechanical or metabolic stress), inflammation, peripheral and central sensitization, degenerative processes (neoangiogenesis, heterotopic ossification, fibrosis), muscle tension, psychoemotional disorders (depression, anxiety), negative behavioral reactions. Pain treatment should be comprehensive and include pharmacotherapy as well as non-pharmacological therapy and rehabilitation methods.Nonsteroidal anti-inflammatory drugs (NSAIDs) are at the forefront of pain treatment. They are effective, convenient and affordable, but can cause a wide range of complications. A personalized approach to pain management is therefore based on the choice of the “right” NSAID. Based on the balance between efficacy and safety, celecoxib can be considered the first choice. It has an extensive evidence base confirming its therapeutic potential in acute pain, osteoarthritis, chronic back pain, systemic rheumatic diseases and other pathologies, as well as a relatively low risk of gastrointestinal and cardiovascular complications. The prescription of celecoxib should be personalized: for severe pain and systemic rheumatic diseases, treatment should be started with a dose of 400 mg/day (600 mg can be used on the first day), followed by a transition to a maintenance dose of 200 mg/day once pain control is achieved.